Influence of Hate Speech on Nigeria’s Political Environment and Voters’ Choice in the 2023 Presidential Election in Nigeria: Implications for Sustainable Development - Ndubuisi Isaac; Francis Chidozie Umendiego; Ogomegbunam Perpetua Anierobi; Sunday Ogbanje; Damian Uzochukwu Attah (CINEFORUM, 2025)
This study examined the influence of political hate speech on voters’ choices during the 2023 Presidential Election in Nigeria and its implication for sustainable development in Nigeria. The study utilized Social Judgment Theory as an analytical framework to explain differing views that voters have about the use of hate speech. Adopting a quantitative survey design, data were procured from both primary and secondary sources, with a sample of 400 voters extracted from a total of 93,469,008 registered voters through a purposive sampling technique. Following the exclusion of 8 responses due to incomplete answers out of 400 copies of questionnaire administered, 392 were returned with complete and accurate responses. Consequently, 392 surveys of response rate of 98.00% were analyzed using Statistical Packages for Social Sciences (SPSS) version (23). Results/findings reveal that hate speech was pervasive across both social and traditional media platforms, constituting 25.5% of documented instances while the overall influence of hate speech on voter behaviour was minimal as 50.5% of participants robustly asserted its effect on voting patterns throughout the election, 15.6% strongly disagreed and 11.0% disagreed, while 11.7% were adjudged to be indifferent. The research further indicated that 49.7% of political actors extensively relied on hate speech during their campaigns. These findings elucidate the deleterious impacts of hate speech on political discourse, as it diminishes candidate credibility, and endangers the integrity of electoral processes. The study recommends that: Electoral regulations prohibiting hate speech be rigorously enforced, media outlets be subjected to scrutiny, and perpetrators be prosecuted. Additionally, politicians are urged to utilize social media judiciously in campaigns. This will ensure that credible leaders are elected to support the realization of the sustainable development goals in Nigeria.